2017
DOI: 10.1080/19768354.2017.1342691
|View full text |Cite
|
Sign up to set email alerts
|

Induction of telomere shortening and cellular apoptosis by sodium meta-arsenite in human cancer cell lines

Abstract: The present study assessed the cytotoxicity of sodium meta-arsenite (SMA) on telomere shortening and cellular apoptosis in human A-549, MDA-MB-231 and U87-MG cancer cell lines. Following 2 weeks of 1 μM SMA treatment, population doubling time (PDT) was significantly (P < .05) increased by the inhibition of cell proliferation in all the cancer cell lines compared to that in untreated controls. Level of telomerase activity by relative-quantitative telomerase repeat amplification protocol was significantly (P < .… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 55 publications
(86 reference statements)
0
13
0
Order By: Relevance
“…However, our results have demonstrated that growth inhibition is associated with the cellular differentiation into adipocyte-like cells rather than apoptosis in A-549 lung and MCF-7 cancer cells after being exposed to DEX at a concentration of 1 μg/ml. The high expression of SA β-gal activity is considered to be a marker of cellular aging and senescence preceding cellular apoptosis (Moon et al 2015 ; Kim et al 2017 ). In the present study, the activity of SA β-gal was not elevated in cancer cells treated with DEX, implying that the cellular senescence or apoptosis might not be induced by DEX exposure.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, our results have demonstrated that growth inhibition is associated with the cellular differentiation into adipocyte-like cells rather than apoptosis in A-549 lung and MCF-7 cancer cells after being exposed to DEX at a concentration of 1 μg/ml. The high expression of SA β-gal activity is considered to be a marker of cellular aging and senescence preceding cellular apoptosis (Moon et al 2015 ; Kim et al 2017 ). In the present study, the activity of SA β-gal was not elevated in cancer cells treated with DEX, implying that the cellular senescence or apoptosis might not be induced by DEX exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The expression level of the transcripts in each sample was calculated in relative to the expression level of a reference gene glyceraldehyde 3-phosphate dehydrogenase (GAPDH). The sequences of primer used in this study were GAPDH and telomerase reverse transcriptase (TERT) related to telomerase activity were previously described (Kim et al, 2017 ). The primers for adipogenesis were glucose transporter 4 (GLUT4, sense: ATGCTGCTGCCTCCTATGAA, antisense: CAGTTGGTTGAGCGTCCC), glucocorticoid receptor β (GRβ, sense: GAAGGAAACTCCAGCCAGAAC, antisense: TGAGCGCCAAGATTGTTGG) and peroxisome proliferator-activated receptor γ (PPARγ, sense: CCTATTGACCCAGAAAGCGATT, antisense: CATTACGGAGAGATCCACGGA), and the size of PCR products was 146, 140 and 135 bp, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Arsenite exposure has been shown to activate ISR signaling through eIF2α phosphorylation and SGs formation . In addition, it has been demonstrated that arsenite influences various cellular processes like apoptosis, proliferation, inflammation, angiogenesis, and immune response . Therapeutically, arsenic compounds have often been used in traditional Chinese and Western medicine for decades to treat several diseases including tooth diseases, rheumatosis, psoriasis, syphilis, and trypanosomiasis .…”
Section: Introductionmentioning
confidence: 99%